2017
DOI: 10.1111/1467-8454.12086
|View full text |Cite
|
Sign up to set email alerts
|

Government Size and Stochastic Growth

Abstract: This paper analyses the effects of the size of government on economic growth in a stochastic endogenous growth model involving the supply-side effect and demand-side effect produced by government spending. We show that a rise in the government spending affects economic growth through three channels, including the crowding-out effect, the spin-off effect and the resource mobilisation effect. We demonstrate that there exists an optimal size of government that maximises the economic growth rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Therefore, Kosempel (2004) said that Barro curve considers only "second-type expenditure" while first "type-expenditure" adversely impacts the economic growth always. Further, Lee et al (2017) considering all these studies, and proposed a theoretical model which contained both consumer side (demand) and producer side (supply) expenditures, and reached to the three channels through which economic growth altered by expenditure which are as follows: First, crowding effect, second, spinoff effect, and third, resources mobilization effect (see for more details, Lee et al, 2017). From these theoretical models described above, we observed that the relationship between "government size and economic growth" alters with respect to the type of expenditures (for instance capital expenditure, revenue expenditure, and social sector government expenditure).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, Kosempel (2004) said that Barro curve considers only "second-type expenditure" while first "type-expenditure" adversely impacts the economic growth always. Further, Lee et al (2017) considering all these studies, and proposed a theoretical model which contained both consumer side (demand) and producer side (supply) expenditures, and reached to the three channels through which economic growth altered by expenditure which are as follows: First, crowding effect, second, spinoff effect, and third, resources mobilization effect (see for more details, Lee et al, 2017). From these theoretical models described above, we observed that the relationship between "government size and economic growth" alters with respect to the type of expenditures (for instance capital expenditure, revenue expenditure, and social sector government expenditure).…”
Section: Introductionmentioning
confidence: 95%
“…Third, once the optimum government size is examined, then this study disaggregates total expenditure into three broad compositions (revenue expenditures, 4 capital expenditure, 5 and social sector expenditures 6 ), and study the "optimum government size" of these compositions and their impact on economic growth as revenue expenditure is growing faster than capital and social sector expenditure across Indian states. 7 The other reason of disaggregating government size into three main compositions because the recent theoretical literature 8 describes that the relationship between "government size and economic growth" alter with respect to types of expenditure (Barro, 1990;Ghosh and Mourmouras, 2002;Kosempel, 2004;Agenor, 2010;Lee et al, 2017).…”
Section: Introductionmentioning
confidence: 99%